Reducing the Impact of Pandemic on Chinese Language Education in the Philippines through the Localization of Chinese Teachers - Pamintuan, Cavin F (Universitas Negeri Makassar, 2021)
This descriptive research focused on the localization of Chinese teachers in the Philippines and how it became instrumental in reducing the impact of COVID-19 pandemic on Chinese language education. Through the review of existing studies and pertinent documents such as memorandum orders, agreements and training plans, this paper provided an in-depth analysis of the current situation of localization of Chinese teachers. Currently, there were three (3) modes of cultivating local teachers for Chinese language teaching, namely in-service teachers’ training, undergraduate degree program and master’s degree program. The mentioned programs have been successful in producing local teachers who are capable of teaching Chinese as a foreign language. Furthermore, it is through the local teachers that the impacts of the pandemic on Chinese language education in the Philippines have been reduced. The localization of Chinese teachers has been of great help in addressing the challenge of not having volunteer Chinese teachers and uniformed instructional materials in the midst of pandemic. Moreover, opportunities for the localization of Chinese teachers were also discussed. Lastly, guided with the findings and conclusions, the paper provided recommendations for further development of Chinese language education in times of pandemic or other natural calamities which may disrupt the face-to-face classes.